A Study of Chemical Composition for Muscles in two Species of Marine Teleosts Fishes: Hilsa Shad, Tenualosa Ilisha and Gizarred Shad, Nematolosa Nasus - Akeil Jameil Mansour (Journal of Global Pharma Technology, 2018)
A comparative study was conducted on the chemical composition for muscles in two types of marine teleosts species; Halsa Shad, Tenualosa ilisha (Hamilton, 1822) and gizzard shad, Nematalosa nasus (Bloch, 1795). The study samples were collected from the Faw market in southern Basra - Iraq between November - 2017 and December - 2018. The results showed a difference in the chemical composition for muscles of the studied fish. Moisture content had high averages ranged between 69 - 71% while there were few averages of ash content which ranged between 1.64-1.99 % . Protein content ranged between 15.98 - 18.90 % while fat content ranged between 7.35-12.05% in the studied species. The results showed significant differences (P < 0.05) in the protein, fat and moisture content between the studied species, while the differences were not significant (P > 0.05) when analyzing the results of ash content statistically. Keywords: Hilsa shad, Gizzard shad, Fish muscles, Chemical composition.